THE EFFECT OF USING GIST STRATEGY ON STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXT AT THE TENTH GRADE OF SMA NEGERI 1 PADANGBOLAK IN 2020/2021 ACADEMIC YEAR - Ririn Noviyanti ritonga (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Abstract: The aim of this research are to know: 1) the application of GIST Strategy on teaching reading comprehension of narrative text, 2) the students reading comprehension of narrative text before and after using GIST Strategy, 3) Whether there is any significant effect of GIST Strategy on teaching reading comprehension of narrative text at the tenth Grade of SMA Negeri 1 Padangbolak. This research uses experimental method with the pre-experimental design by using one-group pretest and posttest design. The population of this research was all of the tenth grade students’ of SMA Negeri 1 Padangbolak which consist of 172 students. Sample were X MIA2 which consist of 30 students taken by purposive sampling. In collecting the data the researchers uses observation sheet and test as an instrument. The result of this research: 1) the application of GIST strategy was 3.5, it is categorized “Very Good”. 2) The mean score of the students’ reading comprehension of narrative text before and after using GIST strategy was 43 and it was categorized “fail” and after was 75, it is categorized “good”. The result of data analysis shows that ttest was higher than ttable (ttest18.8>ttable2.04). So, the hypothesis was accepted. It means that, there is any significant effect of GIST Strategy on students’ Reading comprehension of narrative text at the Tenth grade of SMA Negeri 1 Padangbolak. Keywords: GIST Strategy, Reading, Narrative